The clinical and laboratory manifestations of systemic lupus erythematosus - Natalia Gennadyevna Klyukvina; E L Nasonov (Современная ревматология, 2012)
The literature review deals with the clinical and laboratory manifestations of systemic lupus erythematosus (SLE). The data available in the literature and the authors’ experience suggest that it is difficult to verify the valid diagnosis of the disease, in its atypical variants in particular. The correct assessment of the clinical and laboratory manifestations of SLE in each patient, the detection of an exacerbation of the underlying disease and concomitant pathology, the evaluation of the efficiency of performed therapy, and a search for prognostic markers for an outcome are of great value.